Multifocal myxopapillary ependymoma and iatrogenic spinal cord herniation: management options and lessons learned - Ayesha Arshad; Sheheryar Hanif; Irfana Ishaq Sindhu; Irfan Yousaf (Journal of the Pakistan Medical Association, 2022)
Although myxopapillary ependymoma is a fairly common tumour of the lumbosacral spine, primary multi-focal myxopapillary ependymoma is a rare variant. Drop metastasis and leptomeningeal spread in the craniospinal axis is seen more frequently in the paediatric population, although it is unusual in adults. Surgical resection of the primary lesion remains the standard treatment. As per the authors’ knowledge, to-date there is only one prior case in literature reporting iatrogenic spinal cord herniation with indentation after surgery for thoracolumbar spinal tumour. Here, we are discussing an unusual case of primary multi-focal ependymoma in a 16-year-old Asian boy, with drop metastasis and lepto-meningeal disease, who developed iatrogenic spinal cord herniation after the first surgery for the primary tumour. He presented to the Shaukat Khanum Memorial Cancer Hospital & Research Centre (SKMCH & RC), Lahore, after his first surgery. ---Continue